Prevalence of Gynaecological Disorders under University Ambulatory Clinical Set Up in Gandhinagar, Gujarat - Brahmbhatt, Ankita; Suthar, Vishal; Patel, Jinal; Kapadiya, Falgun; Patil, Deepak B. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The association between gynaecological entities and its management in dairy animals improves reproductive efficiency of animals  and subsequently owner’s wealth. Thus, the objective of this study was to identify gynaecological disorders in milch animals and its  management in an ambulatory set up under Kamdhenu University at Sanoda village located in Dehgam Taluka of Gandhinagar district,  Gujarat. The village has above 3800 animal population. The cases presented for treatment at ambulatory clinics and used in this study  were those reported for the first time. Over the period of three years (July 2017 to March 2020) 2552 bovine cases were categorized  under surgery, medicine and gynaecology and were treated suitably. Of which 1774 (69.51 %) cases were of reproductive disorders, 617  (24.18 %) of medicine and 161 (6.31 %) were of surgery. Out of 1774 reproductive disorders, 1732 cases were of large ruminants. Among  all infertility cases in cattle and buffaloes, the prevalence of endometritis (35.4% / 50.4 %) was highest followed by underdeveloped  genitalia (26.2 % / 14.2 %) and anestrus (18.1 %/ 23.4 %) and to mitigate this case load, there is a need to improve hygienic conditions  while performing scientific AI.
Keywords: Ambulatory Clinic; Dairy animals; Field condition; Gujarat; Prevalence of infertility; Reproductive Disorders